New records of the microdispid mites (Acari: Heterostigmata: Microdispidae) associated with ants with a review of the family in Iran - Hamidreza Hajiqanbar; Mohammad Sobhi (Persian Journal of Acarology, 2018)
Two genera and four species of myrmecophilous microdispid mites (Acari: Heterostigmata: Microdispidae), associated with various ants (Hymenoptera: Formicidae), are recorded from northwestern Iran: Unguidispus japonicus Kurosa, 1979 phoretic on Lasius obscuratus Stitz, 1930, Caesarodispus samsinaki (Mahunka, 1967) on Formica sp., C. modestus (Berlese, 1903) on Messor sp. and C. minutus Sevastianov, 1981 on Tetramorium sp. The species C. samsinaki and U. japonicus are recorded for mite fauna of Iran for the first time. A new ant host record is also documented for U. japonicas. The world distributions of the recorded mites are presented. Moreover, all Iranian microdispid records, along with their host/habitat are reviewed and a key to their genera and species is provided.